Implementing Macroprudential Policy : Selected Legal Issues. (Policy Papers; Policy Paper ;, 2013)
As countries design and implement macroprudential policies, they face the challenge of determining what-if any-changes need to be made to their legal and institutional framework to ensure that these policies are effective. Based on a review of experience, it is clear that there are a variety of approaches that can be taken by members, in light of the legal constraints and institutional preferences of each country. Whichever approach is followed, a number of issues need to be addressed when designing legislation in this area, both with respect to the substantive legal provisions and the allocation of institutional responsibilities. As background to 'Key Aspects of Macroprudential Policy', this paper provides an overview of these legal and institutional issues, while recognizing that macroprudential policy is an area that is still evolving.